Expression Signatures of Long Noncoding RNAs in Left Ventricular Noncompaction - Tian, Qingshan; Niu, Hanxiao; Liu, Dingyang; Ta, Na; Yang, Qing; Norton, Vikram; Wu, Yujing; Maiti, Amit K.; Wu, Hao; Zheng, Zhenzhong (Frontiers in Cardiovascular Medicine, 2021)
Long noncoding RNAs (lncRNAs) have gained widespread attention in recent years as a potentially new and, crucial layer of biological regulation. All kinds of lncRNAs have been implicated in a range of developmental processes and, diseases. Some lncRNAs play critical roles in liver cancer, breast cancer, prostate cancer and other malignant tumors, and, have been identified as disease-specific biomarkers. However, the role of LncRNAs in cardiovascular disease is beginning to unravel and, we investigated the expression levels of lncRNAs in blood of LVNC patients and healthy subjects with Agilent Human lncRNA array that contains both updated LncRNAs and mRNAs probe. 1568 upregulated and 1141 downregulated (logfold-change > 2.0) lncRNAs are identified to be differentially expressed between LVNC and, control group. Among them, RP11-1100L3.7 and, XLOC_002730 are the most upregulated and, downregulated lncRNAs. Using RT-QPCR, we confirmed the differential expression of three top up-regulated and, downregulated lncRNAs along with two other randomly picked LncRNAs from the differentially expressed LncRNAs of microarray. GO and, KEGG pathways analysis with these differentially expressed LncRNAs provide insight into the cellular pathway leading to LVNC pathogenesis. We also identified 1066 upregulated and 1017 downregulated mRNAs. GSEA enrichment analysis showed G2M, Estrogen and inflammatory pathways are enriched in differentially expressed genes. We first report here the use of LncRNA microarray to understand the pathogenesis of LVNC and identify several LncRNA and genes as potential biomarker.